Exposure of Wildlife to the Schmallenberg Virus in France (2011–2014): Higher, Faster, Stronger (than Bluetongue)!. Issue 2 (8th May 2015) - Rossi, S.; Viarouge, C.; Faure, E.; Gilot‐Fromont, E.; Gache, K.; Gibert, P.; Verheyden, H.; Hars, J.; Klein, F.; Maillard, D.; Gauthier, D.; Game, Y.; et al.
Summary: The Schmallenberg virus (SBV) has recently emerged in Europe, causing losses to the domestic livestock. A retrospective analysis of serodata was conducted in France for estimating seroprevalence of SBV among six wildlife species from 2011–2012 to 2013–2014, that is during the three vector seasons after the emergence of the SBV in France. Our objective was to quantify the exposure of wildlife to SBV and the potential protective effect of elevation such as previously observed for bluetongue. We also compared the spatiotemporal trends between domestic and wild animals at the level of the departments. We tested 2050 sera using competitive ELISA tests. Individual and population risk factors were further tested using general linear models among 1934 individuals. All populations but one exhibited positive results, seroprevalence up to 30% being observed for all species. The average seroprevalence did not differ between species but ranged from 0 to 90% according to the area and period, due to the dynamic pattern of infection. Seroprevalence was on average higher in the lowlands compared to areas located up to 800 m. Nevertheless, seroprevalence above 50% occurred in areas located up to 1500 m. Thus, contrary to what had been observed for bluetongue during the late 2000s in the same areas, SBV could spread to high altitudes and infect all the studied species. The spatial spread of SBV in wildlife did not fully match with SBV outbreaks reported in the domestic livestock. The mismatch was most obvious in mountainous areas where outbreaks in wildlife occurred on average one year after the peak of congenital cases in livestock. These results suggest a much larger spread and vector capacity for SBV than for bluetongue virus in natural areas. Potential consequences for wildlife dynamics are discussed.